Financial Intermediary Lending Behavior in the Postwar Canadian Mortgage Market - Smith, Lawrence B. (Quarterly Journal of Economics, 1967)
I. Financial intermediary investment behavior, 494. — II. Long-run trends and structural shifts in the postwar mortgage market, 500. — III. Financial intermediary mortgage investment behavior, 503. — IV. Conclusions, 513.